Implementasi Bimbingan Individu bagi Anak Jalanan melalui Program Patroli Wilayah Sosial oleh Dinas Sosial dan Pemberdayaan Masyarakat Desa Provinsi Kepulauan Bangka Belitung - Apriyadi, Abi (Department of Islamic Guidance and Counseling, 2024)
The purpose of this research to determine the various obstacles experienced by One of the social problems Related to the public policy field Social welfare is a problem for street children. Presence of children Roads on public facilities can cause various traffic problems and urban security. The purpose of this research is to determine the role and results from individual guidance for street children through social area patrol programs by the Islands Province Village Social and Community Empowerment Service Bangka Belitung. This research uses qualitative research methods with types field research. The subjects in this research were two people The supervisors are social workers (Peksos) with social counselors (Pensos). provide individual guidance and five selected street children purposive sampling. Data collection techniques use interviews and observation. Then the data will be analyzed using domain model analysis Spradley. Data collection is carried out continuously through observation, interviews and documentation. The results of this research explain the treatment carried out for street children by social workers and social workers through the provision of ongoing individual guidance in three stages, namely, the initial stage, the middle stage and the final stage. Post provided individual guidance services there are changes in children such as, changing behavior, discovering one's potential, and establishing independence. So that it prevents children from carrying out activities on the streets, such as previously.